Efficient photodegradation of orange II dye by nickel oxide nanoparticles and nanoclay supported nickel oxide nanocomposite - Naseer Ahmad Khan; Khalid Saeed; Idrees Khan; Tamanna Gul; Muhammad Sadiq; Ala Uddin; Ivar Zekker (Applied Water Science, 2022)
Abstract The Nickel oxide nanoparticles (NiO NPs) and Nickel oxide/Nanoclay nanocomposite (NiO/Nc NC) were synthesized by chemical reduction method and used for the photodegradation of Orange II dyes in aqueous solution. The synthesized samples were characterized through SEM, EDX, FTIR and TGA. The SEM analysis presented that the NiO NPs are spherical with irregular shapes and sizes. The size of particles is in the range of 100–400 nm. It was also observed that the NiO NPs are deposited on the surface of Nanoclay. The EDX study confirmed the formation of metal NPs and verify and purity. The FT-IR spectra of NiO and NiO/Nc NC presented peaks at 432 cm−1 and 504 cm−1, which correspond to NiO while peak at 1090–940 cm−1 is due to Si–O stretching vibration of orthosilicate anions and Si–O–Al groups. The photodegradation study illustrated that the NiO NPs and NiO/Nc NC degraded about 93 and 96% Orange II in aqueous medium, respectively within 20 min. The effect of various parameters like initial concentration of dyes, pH, recycled catalysts, and catalyst dosage were also studied.